Konfiksasi Pembentuk Nomina dalam Novel Religius - Gauri, Darma; Liusti, Siti Ainim (TSAQOFAH, 2026)
Research on affixation in Indonesian has been widely conducted; however, studies that specifically map nominal-forming circumfixation in religious novels remain limited. This study aims to describe the types of circumfixes, base forms, and patterns of noun formation through circumfixation in the novels Jilbab Traveler: Love Sparks in Korea by Asma Nadia and Cinta Suci Zahrana by Habiburrahman El-Shirazy. This research employed a descriptive qualitative approach with a corpus-based document analysis design using Kortara, with purposively selected data consisting of circumfixed words and their sentential contexts. The findings show 430 instances of nominal-forming circumfixes, comprising ke-…-an (260 data points), pe-…-an (86 data points), and per-…-an (84 data points). The circumfix ke-…-an is the most productive and predominantly forms abstract nouns denoting states or qualities; pe-…-an tends to form nouns denoting processes or results of actions; while per-…-an forms nouns referring to places or outcomes of activities. In addition, seven patterns of noun formation through circumfixation were identified, with the pattern ke-…-an + D(A) → N being the most dominant, alongside allomorphic variation in pe-…-an (pen-, pem-, peng-). These findings underscore the role of circumfixation in naming abstract concepts that are salient within religious narratives and strengthen the understanding of morphological productivity in religiously nuanced novels.